UNDANG UNDANGNOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL DALAM PERSPEKTIF LIBERAL KLASIK - Alamsyah, Anggryany (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2013)
The preamble of Indonesian Fundamental Laws year 1945 stipulated that the independence of the Indonesian state was basically aimed “…to form a Government of the State of Indonesia that shall protect the whole people of Indonesia and the entire homeland of Indonesia, and in order to advance general prosperity, to develop the nation’s intellectual life, and to contribute to the implementation of a world order based on freedom, lasting peace and social justice…” This part of the preamble means that every public policy in this country should always put hard efforts to reach those goals. Public policies that are not in line with the need of the citizens are apparently having no actual meaning for them. Those policies should be applicable and worthy for all aspects of their life. Laws number 25 year 2007 was passed with spirit “to create a condusive capital investment,” while Laws number 25 year 2007 has explicitly showed that for our government, investment is everything; it is the only way to prosper Indonesian citizens. Clark has concluded that self-interested behavior motivates individuals and firms to compete in the free market. It also drives them to form groups and to seek government protection against competitive pressures and instable markets.